A guide to developing quantitative tools for measuring gender norms in agrifood systems - Seymour, Greg; Cole, Steven M.; Costenbader, Elizabeth; Mwakanyamale, Devis; Adeyeye, Olajumoke; Feleke, Shiferaw; Ferguson, Nathaniel; Heckert, Jessica (International Food Policy Research Institute, 2024)
Increasingly, gender transformative approaches (GTAs), which seek to transform the underlying causes of gender inequalities, including discriminatory gender norms, are being used in agrifood systems (AFS) interventions. A growing body of evidence finds that GTAs contribute to positive impacts on a wide range of important development outcomes and have potential for improving gender equality. One limitation to better understanding changes in AFS-based gender norms as a result of GTAs is a lack of appropriate quantitative tools for measuring these norms. This work is an important step in filling that gap. Herein we detail the collaborative process that we undertook in Nigeria and Tanzania to develop a quantitative approach to measuring gender norms in the cassava, poultry, and fisheries value chains in each country. We then provide guidance for how implementing and research partners using GTAs in AFS can apply our learnings to their own work.